The use of computer-aided process design and simulation tools in undergraduate research projects - Kumaresan, Sivakumar; Foo, Dominic Chwan Yee; Abdul Aziz, Ramlan; Sarmidi, Mohamad Roji (2005)
This paper demonstrates the use of computer-aided process design (CAPD) tools in guiding undergraduate research projects. Over the past two years, SuperPro Designer, a batch process simulation software has been integrated into the one-year undergraduate research projects at the Chemical Engineering Pilot Plant, Universiti Teknologi Malaysia (CEPP, UTM). Four different research projects were successfully carried out and it was found out that the CAPD tools serve as good educational concept in delivering different modes of learning. It was also found that through the use of simulation software that the students underwent all six levels of Blooms Hierarchy of learning.